Framing the ultimatum game: the contribution of simulation - Tomasino, Barbara; Lotto, Lorella; Sarlo, Michela; Civai, Claudia; Rumiati, Rino; Rumiati, Raffaella I. (Frontiers in Human Neuroscience, 2013)
It has now become widely accepted that economic decisions are influenced by cognitive and emotional processes. In the present study, we aimed at disentangling the neural mechanisms associated with the way in which the information is formulated, i.e., framing effect, in terms of gain or loss, which influences people’s decisions. Participants played a fMRI version of the Ultimatum Game where we manipulated bids through two different frames: the expression "I give you" (gain) focusing on money the respondent would receive if she/he agreed with the proponent, and the expression "I take" (loss) focusing on the money that would be removed from the respondent in the event that she/he accepted the offer. Neuroimaging data revealed a frame by response interaction, showing an increase of neural activity in the right rolandic operculum/insular cortex, the anterior cingulate, among other regions, for accepting the frame “I take” vs. rejecting, as compared to accepting the frame “I give you” vs. rejecting. In addition, the left occipito-temporal junction was activated for ‘I take” vs. “I give you” for offer 5, corresponding to the equal offer made unpleasant by the presence of the frame “I take”, where is the proposer that takes the money. Our data extend the current understanding of the neural substrates of social decision making, by disentangling the structures sensitive to the way in which the information is formulated (i.e., framing effect), in terms of gain or loss.